Effects of diagenesis on quality of deep dolomite reservoirs: A case study of the Upper Cambrian Xixiangchi Formation in the eastern Sichuan Basin, China - Ren, Guanxiong; Qin, Qirong; Qin, Zhangjin; Guo, Yanbo; Ye, Zhaoyang (Frontiers in Earth Science, 2022)
With the Upper Cambrian Xixiangchi Formation in the eastern Sichuan Basin as the target, this study investigates various diagenetic events during different diagenetic stages in deep dolomite reservoirs, accompanied by evaluations of their effects on the formation and evolution of the reservoir rock. A series of experiments are implemented on core and outcrop samples, including petrologic analysis, fluid inclusion analysis, rare earth and minor element investigation, and carbon and oxygen isotope test. During the syngenetic (syndepositional and penecontemporaneous) diagenesis stage, dolomitization is closely related to evaporation concentration and seepage reflux of high-salinity seawater, which facilitates the reservoir rock development by greatly enhancing the permeability of the reservoir. Meanwhile, a small number of secondary pores are generated in the sediments subjected to episodic atmospheric exposure and thus affected by meteoric water. During the early diagenesis stage, recrystallization transforms part of the granular dolomite into the crystalline dolomite with or without the phantom of the grain texture. It also alters the original rock’s pore structure and improves the effective primary porosity. Thus, recrystallization is key in forming the crystalline dolomite reservoir rock. However, compaction, cementation, and filling lead to the loss of massive early-formed primary pores and some secondary pores. During the mesodiagenesis-late diagenesis stage, the burial karstification, related to organic matter maturation, is the most direct control factor of the effective reservoirs space formation, and its alteration effect on the reservoir rock is related to the early process. This research helps to better identify the impact of various diagenetic processes during different diagenetic stages upon the formation and evolution of the deep dolomite reservoir rock, and it also helps analyze the relationships among these diagenetic processes. The findings of this research provide valuable references for investigating the formation mechanism of the deep dolomite reservoir rock in the Sichuan Basin.